Solder paste, method for preparing ceramic copper-clad laminate, and ceramic copper-clad laminate

By replacing silver-copper-titanium alloy powder with metal compounds and metal alloy powder, and adopting targeted adhesive system and silk-printing technology, the problems of high welding reliability and cost of ceramic copper clad plates are solved, and the ceramic matrix and copper layer are realized Firm welding and low cost production.

CN117506235BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210908208.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-01-14
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

In the existing ceramic copper clad active metal brazing technology, the welding reliability is poor, the solder paste is difficult to preserve, and the silver-copper-titanium alloy welding sheet is difficult to prepare and the production cost is high, which limits its application prospects.

Method used

Use metal compounds and metal alloy powder to replace silver-copper-titanium ternary alloy powder as solder. By matching suitable adhesive systems and secondary silk screen printing technology for different powders, the first and second solder pastes are formed to improve the solder pastes. Distribution uniformity and stability to achieve good welding of the ceramic substrate and the copper layer.

Benefits of technology

The cost of solder raw materials is reduced by about 50%, the welding strength and reliability are improved, the defects of solder paste in subsequent processes are reduced, and the low-cost and efficient preparation of ceramic copper clad plates is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117506235B_ABST
    Figure CN117506235B_ABST
Patent Text Reader

Abstract

The present application discloses a solder paste, a method for preparing a ceramic copper-clad laminate, and a ceramic copper-clad laminate. The solder paste includes a first solder paste and a second solder paste. The first solder paste includes a metal compound and a first binder. The metal compound includes at least one of a titanium compound, a zirconium compound, and a hafnium compound. The second solder paste includes a metal alloy and a second binder. The dispersibility of the metal compound in the first binder is better than the dispersibility of the metal compound in the second binder. The stability of the metal alloy in the second binder is better than the stability of the metal alloy in the first binder. Thus, good welding between the ceramic substrate and the copper layer can be achieved relatively firmly and at low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of power electronics technology, and in particular, to a solder paste, a method for preparing a ceramic copper clad laminate, and a ceramic copper clad laminate. Background Art

[0002] Ceramic copper-clad laminates have the advantages of high strength, good chemical stability, and high thermal conductivity. They are ideal substrate materials for power devices and can provide physical support for chips, connect circuits, and form heat dissipation channels. Related technologies for connecting ceramics and copper foil include surface copper plating technology, direct copper plating technology, chemical copper plating technology, and active metal brazing technology. Among them, active metal brazing has the advantages of strong copper plating ability, long hot and cold shock cycle life, and high peeling strength. Its reliability is significantly better than other technical processes. Active metal brazing for ceramic copper-clad laminates still has problems such as poor welding reliability and difficulty in preserving solder paste.

[0003] Therefore, the current solder paste, method for preparing ceramic copper clad laminate and ceramic copper clad laminate still need to be improved. Summary of the invention

[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0005] In the related art, silver-copper-titanium alloy welding sheets or silver-copper-titanium solder pastes are usually selected as solders for active metal brazing of ceramic copper-clad laminates. The inventors found that due to problems such as titanium oxidation, segregation and alloy processing brittleness, the preparation of silver-copper-titanium alloy welding sheets is difficult and not conducive to large-scale use; silver-copper-titanium active solder pastes require silver-copper-titanium ternary alloy powder as the preparation raw material, and the preparation process of the alloy powder is complicated and the production cost is high, which greatly limits the application prospects of the silver-copper-titanium active solder paste.

[0006] The present application aims to alleviate or solve at least one of the above-mentioned problems to at least some extent.

[0007] In one aspect of the present application, the present application proposes a solder paste, including a first solder paste and a second solder paste, wherein the first solder paste includes a metal compound and a first binder, wherein the metal compound includes at least one of a titanium compound, a zirconium compound, and a hafnium compound; the second solder paste includes a metal alloy and a second binder, wherein the dispersibility of the metal compound in the first binder is better than the dispersibility of the metal compound in the second binder; and the stability of the metal alloy in the second binder is better than the stability of the metal alloy in the first binder. Thus, good welding of the ceramic substrate and the copper layer can be achieved relatively firmly and at low cost.

[0008] In another aspect of the present application, the present application proposes a method for preparing a ceramic copper-clad laminate, comprising: providing a ceramic substrate; setting a solder paste on the surface of the ceramic substrate, the solder paste being the aforementioned solder paste; setting a copper layer on the surface of the solder paste away from the ceramic substrate, and performing a brazing process to obtain the ceramic copper-clad laminate, wherein the setting of the solder paste comprises: providing a first solder paste and a second solder paste; setting one of the first solder paste or the second solder paste on the surface of the ceramic substrate, and setting the other of the first solder paste or the second solder paste on the surface of one of the first solder paste or the second solder paste away from the ceramic substrate. Thus, good welding between the ceramic substrate and the copper layer can be achieved, and a ceramic copper-clad laminate with excellent performance can be obtained.

[0009] In another aspect of the present application, the present application proposes a ceramic copper clad laminate prepared by the aforementioned method, thereby the ceramic copper clad laminate has all the characteristics and advantages of the aforementioned method, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0011] Figure 1 A schematic diagram of a process for preparing a ceramic copper-clad laminate according to an embodiment of the present application is shown;

[0012] Figure 2 A schematic diagram of the structure of a ceramic copper clad laminate according to an embodiment of the present application is shown;

[0013] Figure 3 A schematic structural diagram of a ceramic copper clad laminate according to another embodiment of the present application is shown.

[0014] Description of reference numerals:

[0015] 100: ceramic substrate; 200: welding layer; 300: copper layer. DETAILED DESCRIPTION

[0016] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0017] In one aspect of the present application, the present application proposes a solder paste, including a first solder paste and a second solder paste, wherein the first solder paste includes a metal compound and a first binder, wherein the metal compound includes at least one of a titanium compound, a zirconium compound, and a hafnium compound; the second solder paste includes a metal alloy and a second binder, wherein the dispersibility of the metal compound in the first binder is better than the dispersibility of the metal compound in the second binder; and the stability of the metal alloy in the second binder is better than the stability of the metal alloy in the first binder. Thus, good welding between the ceramic substrate and the copper layer can be achieved relatively firmly and at low cost.

[0018] For ease of understanding, the principle of the method for preparing a ceramic copper clad laminate in the present application having the above-mentioned beneficial effects is explained below:

[0019] In the related art, silver-copper-titanium alloy welding sheets or silver-copper-titanium active solder pastes are usually used as solders for active metal brazing of ceramic copper-clad laminates. However, the preparation process of silver-copper-titanium ternary alloy materials is difficult and costly. Compared with silver-copper-titanium ternary alloy powders, the preparation processes of metal compound powders and metal alloy powders are relatively simple and the production cost is high.

[0020] In the present application, the inventors found that by using metal compound powder and metal alloy powder instead of silver-copper-titanium ternary alloy powder as the solder for active metal brazing of ceramic copper-clad plates, the cost of solder raw materials can be reduced by about 50%. In addition, since the ratio of the three metal elements in the silver-copper-titanium ternary alloy powder is fixed, it is not possible to easily adjust the ratio of any metal element in the alloy powder alone to enhance the effect of a certain metal element on the welding strength.

[0021] Furthermore, the inventors have also found that due to the large differences in properties such as shape, particle size and density between metal compound powder and metal alloy powder, there are significant differences in the dispersibility and stability of the two powders in the same slurry system, and there are differences in the composition of the optimal binder systems corresponding to the two powders. If the two powders are mixed to prepare a single-component solder paste, problems such as poor distribution uniformity and severe sedimentation and stratification of the two powders will occur, resulting in defects such as flower blooming and voids in the solder paste during subsequent processes such as screen printing and sintering. Therefore, in the present application, a first solder paste and a second solder paste are formed for the metal compound powder and the metal alloy powder, respectively. By matching the appropriate binder system for the two powders and adopting a secondary screen printing method, a solder paste containing a metal compound and a solder paste containing a metal alloy are added step by step and multiple times, so that the solder paste has a higher distribution uniformity and stability. When setting the solder paste, the amount of the metal compound and the metal alloy in the welding layer can also be flexibly adjusted, thereby adjusting the proportion of a certain element in the three elements. For example, when the metal compound is titanium hydride or zirconium hydride and the alloy powder is silver-copper alloy, the titanium and zirconium elements can react chemically with the ceramic matrix to generate titanium nitride, titanium silicide, zirconium nitride and zirconium silicide and other compounds to enhance the welding strength with the ceramic matrix, and can also promote the spreading of silver-copper eutectic to enhance the welding strength with the copper layer. Therefore, the brazing quality can be effectively improved by adjusting the proportion of titanium and / or zirconium in the welding layer.

[0022] According to some embodiments of the present application, the type of metal compound in the solder paste is not particularly limited. For example, the titanium compound may include at least one of titanium boride, titanium hydride, titanium sulfide and titanium tetrachloride, the zirconium compound may include at least one of zirconium boride, zirconium hydride, zirconium sulfide, zirconium tetrachloride and zirconium hydroxide, and the hafnium compound may include at least one of hafnium boride, hafnium hydride, hafnium sulfide and hafnium tetrachloride. Preferably, the metal compound may include at least one of titanium hydride, titanium boride and zirconium hydride.

[0023] According to some embodiments of the present application, the particle size of the metal compound in the first solder paste is not particularly limited, for example, the particle size of the metal compound can be 1-20 microns, further, can be 1-5 microns, and further, preferably 1-3 microns. When the particle size of the metal compound is less than 1 micron, the specific surface area of ​​the metal compound is too large, and a large amount of binder is required for dispersion to completely wet the surface of the metal compound particles, so that the viscosity of the first solder paste is relatively large and the screen printing performance is poor; when the particle size of the metal compound is greater than 20 microns, the gap between adjacent metal compound particles in the first solder paste is large, and the uniformity and leveling of the surface to be soldered formed by screen printing are poor.

[0024] According to some embodiments of the present application, the particle size of the metal alloy in the second solder paste is not particularly limited, for example, the particle size of the metal alloy may be 5-50 microns, further, may be 5-30 microns, and further, preferably 5-20 microns. When the particle size of the metal alloy is less than 5 microns, the specific surface area of ​​the metal alloy is too large, and a large amount of binder is required for dispersion to completely wet the surface of the metal alloy particles, so that the viscosity of the second solder paste is relatively large and the screen printing performance is poor; when the particle size of the metal alloy is greater than 50 microns, the gap between adjacent metal alloy particles in the second solder paste is large, and the uniformity and leveling of the surface to be soldered formed by screen printing are poor.

[0025] According to some embodiments of the present application, the composition of the first binder is not particularly limited. For example, the first binder may include 85-95wt% of a solvent, 1-10wt% of a dispersant, 1-7.5wt% of a thickener, 0.1-0.5wt% of a surfactant, and 0-5wt% of a thixotropic agent. According to some embodiments of the present application, the solvent in the first binder may include one or more of pineneol, tributyl citrate, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate; the dispersant may include one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200, and polyethylene glycol 400; the thickener may include one or more of ethyl cellulose, polyvinyl alcohol, and acrylic resin; the surfactant may include one or more of Tween 20, Span 80, and sodium dodecylbenzene sulfonate; the thixotropic agent may include one or more of polyamide wax, modified polyurea, and hydrogenated castor oil. Since the density and particle size of the metal compound powder are small, the difficulty in preparing the first solder paste lies in the dispersion of the powder. Therefore, the first binder is required to have a higher dispersant dosage and a lower viscosity, that is, a higher solvent dosage and a lower thickener dosage, and the thixotropic agent can be added selectively.

[0026] In this application, all the numbers disclosed herein are approximate values, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0027] According to some embodiments of the present application, the composition of the second binder is not particularly limited. For example, the second binder may include 80-93wt% of a solvent, 1-7.5wt% of a dispersant, 3-10wt% of a thickener, 0.1-0.5wt% of a surfactant, and 0.5-5wt% of a thixotropic agent. According to some embodiments of the present application, the solvent in the second binder may include one or more of pineol, tributyl citrate, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate; the dispersant may include one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200, and polyethylene glycol 400; the thickener may include one or more of ethyl cellulose, polyvinyl alcohol, and acrylic resin; the surfactant may include one or more of Tween 20, Span 80, and sodium dodecylbenzene sulfonate; the thixotropic agent may include one or more of polyamide wax, modified polyurea, and hydrogenated castor oil. Since the metal alloy powder has a large density and particle size, it has a significant tendency to settle downward in the solder paste. Therefore, it is necessary to appropriately increase the viscosity and thixotropy of the second binder to ensure the stability of the second solder paste. Therefore, a lower solvent dosage and a higher thickener dosage are used, and an appropriate amount of thixotropic agent must be added, so as to reduce the sedimentation rate of the solder paste by adding the thixotropic agent.

[0028] According to some embodiments of the present application, the mass fraction of the metal compound in the first solder paste is not particularly limited. For example, the mass fraction of the metal compound in the first solder paste can be 40-70wt%. The proportion of the metal compound in the first solder paste determines the quality of brazing. When the mass fraction of the metal compound in the first solder paste is less than 40wt%, the metal elements in the metal compound cannot completely react with the surface of the nitride ceramic; when the mass fraction of the metal compound in the first solder paste is greater than 70wt%, the thickness of the transition layer structure at the contact surface between the final welding layer and the ceramic substrate is relatively thick, and the linear expansion coefficients of the transition layer and the ceramic substrate are inconsistent, which significantly increases the difficulty of etching the ceramic copper clad laminate.

[0029] According to some embodiments of the present application, the mass fraction of the metal alloy in the second solder paste is not particularly limited. For example, the mass fraction of the metal alloy in the second solder paste can be 80-90wt%. The proportion of the metal alloy in the second solder paste determines the quality of brazing. When the mass fraction of the metal alloy in the second solder paste is less than 80wt%, the silver and copper elements in the metal alloy cannot form a eutectic spreading with the copper layer; when the mass fraction of the metal alloy in the second solder paste is greater than 90wt%, the thickness of the transition layer structure at the contact between the welding layer and the copper layer is relatively thick, and the linear expansion coefficients of the transition layer and the copper layer are inconsistent, resulting in poor holes inside the ceramic copper clad laminate.

[0030] In another aspect of the present application, the present application proposes a method for preparing a ceramic copper-clad laminate, comprising: providing a ceramic substrate; setting a solder paste on the surface of the ceramic substrate, the solder paste being the aforementioned solder paste; setting a copper layer on the surface of the solder paste away from the ceramic substrate, and performing a brazing process to obtain a ceramic copper-clad laminate, wherein setting the solder paste comprises: providing a first solder paste and a second solder paste; setting one of the first solder paste or the second solder paste on the surface of the ceramic substrate, and setting the other of the first solder paste or the second solder paste on the surface of one of the first solder paste or the second solder paste away from the ceramic substrate. Thus, good welding between the ceramic substrate and the copper layer can be achieved, and a ceramic copper-clad laminate with excellent performance can be obtained.

[0031] It should be particularly noted that in the present application, the inventors found that because the solder paste needs to be subjected to high temperature treatment during the brazing process, the two solder pastes will melt and mix, and finally be evenly dispersed in the welding layer. Therefore, the welding strength of the welding layer finally obtained by first applying a solder paste containing a metal compound on the surface of the ceramic substrate and then applying a solder paste containing a metal alloy is similar to that of first applying a solder paste containing a metal alloy on the surface of the ceramic substrate and then applying a solder paste containing a metal compound. That is, in the present application, as long as the solder paste containing a metal compound and the solder paste containing a metal alloy are applied in steps, the aforementioned beneficial effect of achieving good welding between the ceramic substrate and the copper layer at a low cost can be obtained. The order of applying the two solder pastes is not particularly limited, and those skilled in the art can choose according to actual conditions.

[0032] Specifically, refer to Figure 1 Taking the example of first setting a first solder paste on the surface of a ceramic substrate and then setting a second solder paste, the method for preparing a ceramic copper clad laminate may include the following steps:

[0033] S100: Provides ceramic substrate

[0034] According to some embodiments of the present application, a ceramic substrate is provided in this step, and the type of the ceramic substrate is not particularly limited. For example, the ceramic substrate may include nitride ceramics, specifically, may include ceramic materials such as silicon nitride and aluminum nitride.

[0035] In the present application, setting solder paste on the surface of the ceramic substrate includes two steps: setting a first solder paste on the surface of the ceramic substrate and setting a second solder paste on the surface of the first solder paste away from the ceramic substrate, wherein one of the first solder paste and the second solder paste includes a metal compound and the other includes a metal alloy. The inventors found that, taking the metal compound as titanium hydride as an example, the titanium element can react with the nitride ceramic substrate and then generate a chemical bonding force with the ceramic substrate, thereby improving the welding strength of the welding layer; taking the metal alloy as a silver-copper alloy as an example, the silver-copper element can form a eutectic spread with the copper element of the copper layer and then generate a chemical bonding force with the copper layer, thereby improving the welding strength of the welding layer.

[0036] In the description of this application, "first feature" or "second feature" may include one or more of the features.

[0037] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0038] According to some embodiments of the present application, the solder paste with metal compounds further includes a first binder, and the solder paste with metal alloys further includes a second binder, wherein the dispersibility of the metal compound in the first binder is better than the dispersibility of the metal compound in the second binder; the stability of the metal alloy in the second binder is better than the stability of the metal alloy in the first binder. Because the density of the metal alloy is large and the density of the metal compound is small, when the two powder materials are dispersed using the same binder, the solder paste is prone to problems such as poor distribution uniformity and severe sedimentation and stratification, resulting in defects such as flower blooming and voids in the subsequent processes such as screen printing and sintering. Therefore, by selecting a first binder with good dispersibility for the metal compound and a second binder with good stability for the metal alloy, the first solder paste and the second solder paste can have good distribution uniformity and stability. Specifically, the first binder can be configured by the following method: first, add a thickener to the solvent and stir at high speed at 60-90°C for 1-2 hours until the thickener is completely dissolved to form a clear and transparent solution. Then add a dispersant and a surfactant and continue stirring for 0.5-1 hour. After stopping stirring, the insoluble impurities are quickly filtered out, and the obtained binder is allowed to stand at room temperature for more than 6 hours to obtain the first binder.

[0039] It is understandable that, during the preparation of the first binder, after the thickener is added to the solvent and completely dissolved, a thixotropic agent can be added to the system, and stirring is continued for 0.5-1 hour at the temperature, and the dispersant and surfactant are added after the thixotropic agent is completely dissolved; or the thixotropic agent may not be added, and the dispersant and surfactant may be directly added after the thickener is completely dissolved in the solvent. The technicians in this field can make the choice according to the actual situation.

[0040] Specifically, the second binder can be configured as follows: first, add the thickener to the solvent, stir at high speed at 60-90°C for 1-2 hours, until the thickener is completely dissolved to form a clear and transparent solution. Then, add the thixotropic agent to the system, continue stirring at this temperature for 0.5-1 hour, and after the thixotropic agent is completely dissolved, add the dispersant and surfactant, and continue stirring for 0.5-1 hour. After stopping stirring, quickly filter to remove insoluble impurities, and the obtained binder is left to stand at room temperature for more than 6 hours to obtain the second binder.

[0041] It is understandable that, based on the consideration that the first solder paste and the second solder paste need to be melted and mixed in the subsequent brazing process, when the content of the components in the first binder and the second binder differ greatly, the melting point difference between the first solder paste and the second solder paste will be large, which will lead to the mixing of the solder pastes and poor welding effect in the subsequent brazing process, and the welding layer is prone to cracks. Therefore, there is a small difference in the type and content of the components between the first binder and the second binder, and the difference in the mass fraction of the same component in the first binder and the second binder is not greater than 10wt%.

[0042] S200: Setting the first solder paste on the surface of the ceramic substrate

[0043] According to some embodiments of the present application, in this step, a first solder paste is provided, and the first solder paste is disposed on the surface of the ceramic substrate. Specifically, providing the first solder paste may include: providing a first binder; dispersing the metal compound in the first binder to obtain the first solder paste. For example, the components of the first binder may be uniformly mixed to form a viscous liquid, and then the metal compound may be uniformly dispersed in the viscous liquid by mechanical stirring and three-roll grinding.

[0044] According to some embodiments of the present application, the proportion of metal compounds in the solder layer can be effectively controlled by controlling the single-sided weight of the first solder paste. Specifically, the single-sided weight of the first solder paste can be 7.5-26.3 g / m 2 Since the mass fraction of the metal compound in the first solder paste is 40-70wt%, the single-sided gram weight of the first solder paste can be controlled within the above range after coating, thereby improving the soldering quality by adjusting the proportion of the metal compound in the soldering layer.

[0045] According to some embodiments of the present application, the process of providing the first solder paste is not particularly limited. For example, the process of providing the first solder paste may include screen printing.

[0046] S300: Disposing a second solder paste on a surface of the first solder paste away from the ceramic substrate

[0047] According to some embodiments of the present application, in this step, a second solder paste is provided, and the second solder paste is disposed on the surface of the first solder paste away from the ceramic substrate. Specifically, providing the second solder paste may include: providing a second binder; dispersing the metal alloy in the second binder to obtain the second solder paste. For example, the components of the second binder may be uniformly mixed to form a viscous liquid, and then the metal alloy may be uniformly dispersed in the viscous liquid by mechanical stirring and three-roll grinding.

[0048] According to some embodiments of the present application, the type of the metal alloy is not particularly limited. For example, the metal alloy may include at least one of a silver-copper alloy, a copper-phosphorus-silver alloy, and a copper-tin-phosphorus-silver alloy.

[0049] According to some embodiments of the present application, the weight of a single side of the second solder paste can be controlled to effectively control the proportion of the metal alloy in the solder layer. Specifically, the weight of a single side of the second solder paste can be 75.2-112.8 g / m 2 Since the mass fraction of the metal compound in the aforementioned second solder paste is 80-90wt%, the single-sided gram weight of the second solder paste can be controlled within the above range after coating, thereby improving the soldering quality by adjusting the proportion of the metal alloy in the soldering layer.

[0050] According to some embodiments of the present application, the process of providing the second solder paste is not particularly limited. For example, the process of providing the second solder paste may include screen printing.

[0051] S400: Copper layer is placed on the side of the solder paste away from the ceramic substrate

[0052] According to some embodiments of the present application, in this step, a copper layer is arranged on the surface of the solder paste away from the ceramic substrate. The type of the copper layer is not particularly limited. For example, the copper layer can be oxygen-free copper foil, and the thickness of the copper foil can be 0.3-0.8 mm.

[0053] S500: Brazing

[0054] According to some embodiments of the present application, in this step, the first solder paste and the second solder paste are subjected to a brazing process to obtain a ceramic copper clad laminate. The process of the brazing process is not particularly limited. For example, when an oxygen-free copper foil is used as the copper layer, the brazing process may be a vacuum brazing process, wherein the temperature of the vacuum brazing process may be 800-900°C, and the time of the vacuum brazing process may be 2-3 hours. By adopting a vacuum brazing process for brazing, oxidation of the metal elements in the metal compound and the copper foil can be prevented.

[0055] In another aspect of the present application, the present application provides a ceramic copper clad laminate prepared by the aforementioned method. Therefore, the ceramic copper clad laminate has all the features and advantages of the aforementioned method, which will not be described in detail here.

[0056] According to some embodiments of the present application, the structure of the ceramic copper clad laminate is not particularly limited. Figure 2 The ceramic copper clad laminate includes: a ceramic substrate 100; a welding layer 200, the welding layer 200 is located on at least one side surface of the ceramic substrate 100, and the welding layer 200 is formed by brazing a first solder paste and a second solder paste; a copper layer 300, and the copper layer 300 is located on one side surface of the welding layer 200 away from the ceramic substrate 100.

[0057] According to some embodiments of the present application, the structure of the ceramic copper clad laminate is not particularly limited. Figure 3The two side surfaces of the ceramic substrate 100 are both provided with a welding layer 200 , and the side surface of the welding layer 200 away from the ceramic substrate 100 is provided with a copper layer 300 .

[0058] It should be noted that the preparation method of the above-mentioned solder paste can refer to some or all of the steps in the above-mentioned preparation method, and the relevant parameters of the above-mentioned metal compounds, metal alloys and adhesives can refer to some or all of the technical features in the above-mentioned embodiments. The parts not described in the solder paste embodiment can also refer to the above-mentioned embodiments and related drawings, and will not be repeated here.

[0059] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0060] Example 1

[0061] 1. Preparation of the first binder: 5.5 wt% of ethyl cellulose was added to a mixed solvent of 83.9 wt% of pine alcohol and 8.5 wt% of tributyl citrate, and stirred at 80°C for 90 min. Then, 1.0 wt% of polyamide wax was added and stirring was continued for 30 min. Subsequently, 1.0 wt% of DISPERBYK-168 and 0.1 wt% of Tween 20 were added. After stirring for 30 min, the mixture was filtered and allowed to stand for use.

[0062] 2. Preparation of the second binder: Add 5.0wt% of ethyl cellulose to a mixed solvent of 74.8wt% of pine alcohol and 14wt% of tributyl citrate, stir at 80°C for 90min, add 1.0wt% of polyamide wax and continue stirring for 30min, then add 5.0wt% of stearic acid and 0.2wt% of Tween 20, stir for 30min, filter and let stand for use.

[0063] 3. Preparation of the first solder paste: Titanium hydride powder with an average particle size of 5.0 microns is mixed with a first binder at a ratio of 50 wt %, and dispersed with a three-roll mill to obtain the first solder paste.

[0064] 4. Preparation of the second solder paste: silver-copper alloy powder with an average particle size of 20.0 μm was mixed with the second binder at a ratio of 85 wt %, and dispersed with a three-roll grinder to obtain the second solder paste.

[0065] 5. Screen print the first solder paste on both sides of the silicon nitride ceramic sheet, and control the single-sided weight to 18.8g / m 2After drying at 80℃ for 15min, the second solder paste was screen printed on the surface of the dried first solder paste, and the single-sided weight was controlled to be 94.0g / m 2 , and dried at 80℃ for 30min. Cover the surface of the welding layer on both sides with oxygen-free copper foil with a thickness of 0.3mm, and place it in a vacuum brazing furnace for degreasing, debinding and sintering, and keep it at 850℃ for 2 hours.

[0066] Embodiment 2:

[0067] 1. Preparation of the first binder: 5.5 wt% of ethyl cellulose was added to a mixed solvent of 75.8 wt% of pine alcohol and 14.5 wt% of tributyl citrate, and stirred at 80°C for 90 min. Then, 1.0 wt% of polyamide wax was added and stirring was continued for 30 min. Subsequently, 3.0 wt% of stearic acid and 0.2 wt% of Tween 20 were added. After stirring for 30 min, the mixture was filtered and allowed to stand for use.

[0068] 2. Preparation of the second binder: Add 5.5wt% of ethyl cellulose to a mixed solvent of 77.3wt% of pine alcohol and 15wt% of tributyl citrate, stir at 80°C for 90min, add 1.0wt% of polyamide wax and continue stirring for 30min, then add 1.0wt% of stearic acid and 0.2wt% of Tween 20, stir for 30min, filter and let stand for use.

[0069] 3. Preparation of the first solder paste: Titanium hydride powder with an average particle size of 5.0 μm was mixed with a first binder at a ratio of 60 wt %, and dispersed using a three-roll mill to obtain the first solder paste.

[0070] 4. Preparation of the second solder paste: silver-copper alloy powder with an average particle size of 20.0 μm was mixed with the second binder at a ratio of 85 wt %, and dispersed with a three-roll grinder to obtain the second solder paste.

[0071] 5. Screen print the second solder paste on both sides of the silicon nitride ceramic sheet, and control the single-sided weight to 90.2g / m 2 After drying at 80℃ for 30min, the first solder paste is screen printed on the surface of the dried second solder paste, and the single-sided weight is controlled to be 11.3g / m 2 , and dried at 80℃ for 15min. Cover the surface of the welding layer on both sides with oxygen-free copper foil with a thickness of 0.8mm, and place it in a vacuum brazing furnace for degreasing, debinding and sintering at a temperature of 900℃ for 3 hours.

[0072] Comparative Example 1:

[0073] Comparative Example 1 is consistent with Example 1, except that the single-sided weight of the first solder paste is controlled to be 45.1 g / m 2 The single-sided weight of the second solder paste is controlled to be 67.7g / m 2 .

[0074] Comparative Example 2:

[0075] 1. Preparation of binder: Add 5.0wt% ethyl cellulose to a mixed solvent of 74.8wt% pine alcohol and 14wt% tributyl citrate, stir at 80°C for 90min, add 1.0wt% polyamide wax and continue stirring for 30min, then add 5.0wt% stearic acid and 0.2wt% Tween 20, stir for 30min, filter and let stand for use.

[0076] 2. Preparation of solder paste: Titanium hydride powder with an average particle size of 5.0 μm and silver-copper alloy powder with an average particle size of 20.0 μm were mixed with a binder in a ratio of 8.3 wt% and 70.8 wt%, respectively, and dispersed with a three-roll grinder to obtain a mixed solder paste.

[0077] 3. Screen print the mixed solder paste on both sides of the silicon nitride ceramic sheet, and control the single-sided weight to 90.2g / m 2 , and dried at 80℃ for 30min. Cover the surface of the welding layer on both sides with oxygen-free copper foil with a thickness of 0.3mm, and place it in a vacuum brazing furnace for degreasing, debinding and sintering, and keep it at 850℃ for 2 hours.

[0078] Comparative Example 3:

[0079] Comparative Example 3 is consistent with Steps 1-4 of Example 1.

[0080] The difference is that the first solder paste and the second solder paste are mixed in a weight ratio of 1:5 and dispersed by a three-roll grinder to obtain a mixed solder paste. The mixed solder paste is screen-printed on both sides of the silicon nitride ceramic sheet, and the single-sided weight is controlled to be 90.2g / m 2 , and dried at 80℃ for 30min. Cover the surface of the welding layer on both sides with oxygen-free copper foil with a thickness of 0.3mm, and place it in a vacuum brazing furnace for degreasing, debinding and sintering, and keep it at 850℃ for 2 hours.

[0081] Test method: The average particle size of the powder is tested by the laser diffraction method of particle size distribution according to GB / T 19077-2016, ultrasonically dispersed in anhydrous ethanol for 5 minutes, tested in industrial alcohol as a dispersion medium, and the D50 particle size is taken as the average particle size. The defective rate of the ceramic copper clad laminate after welding is obtained by calculating the percentage of products with defective holes using the method in GB / T39240-2020 General Principles for Ultrasonic Testing of Nondestructive Testing. The peel strength of the ceramic copper clad laminate is tested using the GB / T 11363-2008 brazing joint strength test method.

[0082] The test results show that the defective rate of holes in the ceramic copper-clad laminate in Example 1 is 1%, and the average peel strength is 18N / mm. The defective rate of holes in the ceramic copper-clad laminate in Example 2 is 1.5%, and the average peel strength is 15N / mm. The defective rate of holes in the ceramic copper-clad laminate in Comparative Example 1 is 9.5%, and the average peel strength is 9N / mm. The silk-screen weight of the two solder pastes in Comparative Example 1 leads to a high content of titanium in the welding layer of the ceramic copper-clad laminate obtained, a low content of silver-copper alloy, and an increase in the thickness of the titanium nitride transition layer and the titanium silicide transition layer generated by the reaction of the welding layer and the silicon nitride ceramic. Due to the large difference in the linear expansion coefficient between the transition layer and the ceramic substrate, more holes are generated between the welding layer and the ceramic substrate; and the low content of silver-copper alloy leads to a weak bonding force between the welding layer and the copper foil, which is generally poor in peel strength. The defective rate of holes in the ceramic copper-clad laminate in Comparative Example 2 is 8.5%, and the average peel strength is 8.4N / mm. The ceramic copper clad laminate in Comparative Example 3 has a hole defect rate of 6% and an average peel strength of 10 N / mm. The ceramic copper clad laminates in Comparative Examples 2 and 3 have obvious color unevenness and blooming after solder paste printing, and there are black wavy or blocky areas, indicating that the titanium hydride and silver-copper alloy powders are not evenly dispersed in the mixed solder paste, resulting in the mixed solder paste having defects such as blooming and voids in the subsequent processes such as screen printing and sintering. The hole defect rate after brazing is high and the peel strength of the welding layer is very low.

[0083] Unless otherwise specified, all scientific and technological terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. All patents and publications related to this application are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the content specified in this application, but does not exclude the content of other aspects.

[0084] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0085] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A solder paste, characterized in that: The invention comprises a first solder paste and a second solder paste, wherein the first solder paste comprises a metal compound and a first binder, wherein the metal compound comprises at least one of a titanium compound, a zirconium compound and a hafnium compound; the second solder paste comprises a metal alloy and a second binder, wherein the dispersibility of the metal compound in the first binder is better than the dispersibility of the metal compound in the second binder; the stability of the metal alloy in the second binder is better than the stability of the metal alloy in the first binder, The first binder comprises 85-95wt% of a solvent, 1-10wt% of a dispersant, 1-7.5wt% of a thickener, 0.1-0.5wt% of a surfactant and 0-5wt% of a thixotropic agent; the second binder comprises 80-93wt% of a solvent, 1-7.5wt% of a dispersant, 3-10wt% of a thickener, 0.1-0.5wt% of a surfactant and 0.5-5wt% of a thixotropic agent, The solder paste is used for brazing of ceramic copper-clad boards, and the first solder paste and the second solder paste are applied in steps during brazing.

2. The solder paste according to claim 1, characterized in that The titanium compound includes at least one of titanium boride, titanium hydride, titanium sulfide and titanium tetrachloride; the zirconium compound includes at least one of zirconium boride, zirconium hydride, zirconium sulfide, zirconium tetrachloride and zirconium hydroxide; the hafnium compound includes at least one of hafnium boride, hafnium hydride, hafnium sulfide and hafnium tetrachloride; and the metal alloy includes at least one of silver-copper alloy, copper-phosphorus-silver alloy and copper-tin-phosphorus-silver alloy.

3. The solder paste according to claim 1, characterized in that The particle size of the metal compound is 1-20 microns, and the particle size of the metal alloy is 5-50 microns.

4. The solder paste according to claim 1, characterized in that The solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; the dispersant includes one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200 and polyethylene glycol 400; the thickener includes one or more of ethyl cellulose, polyvinyl alcohol and acrylic resin; the surfactant includes one or more of Tween 20, Span 80 and sodium dodecylbenzene sulfonate; the thixotropic agent includes one or more of polyamide wax, modified polyurea and hydrogenated castor oil.

5. The solder paste according to claim 1, characterized in that The mass fraction of the metal compound in the first solder paste is 40-70wt%, and the mass fraction of the metal alloy in the second solder paste is 80-90wt%.

6. A method for preparing a ceramic copper-clad laminate, characterized in that: include: providing a ceramic substrate; Disposing solder paste on the surface of the ceramic substrate, wherein the solder paste is the solder paste according to any one of claims 1 to 5; A copper layer is provided on the surface of the solder paste on one side away from the ceramic substrate, and a brazing process is performed to obtain the ceramic copper-clad laminate. Wherein, the setting of solder paste comprises: providing a first solder paste and a second solder paste; One of the first solder paste or the second solder paste is disposed on a surface of the ceramic substrate, and the other of the first solder paste or the second solder paste is disposed on a surface of the one of the first solder paste or the second solder paste away from the ceramic substrate.

7. The method according to claim 6, characterized in that Providing the first solder paste includes: providing a first binder; dispersing the metal compound in the first binder to obtain the first solder paste, and providing the second solder paste includes: providing a second binder; dispersing the metal alloy in the second binder to obtain the second solder paste.

8. The method according to claim 6, characterized in that The single-sided weight of the first solder paste is 7.5-26.3 g / m 2 The single-sided weight of the second solder paste is 75.2-112.8 g / m 2 .

9. The method according to claim 6, characterized in that The process of setting the solder paste includes screen printing, the brazing process includes vacuum brazing process, the temperature of the vacuum brazing process is 800-900° C., and the time of the vacuum brazing process is 2-3 hours.

10. A ceramic copper-clad laminate prepared by the method according to any one of claims 6 to 9.

11. The ceramic copper clad laminate according to claim 10, characterized in that: The ceramic copper-clad laminate comprises: a ceramic substrate; a welding layer, the welding layer is located on at least one side surface of the ceramic substrate, the welding layer is formed by brazing a first solder paste and a second solder paste; and a copper layer, the copper layer is located on a side surface of the welding layer away from the ceramic substrate.

Citation Information

Patent Citations

  • Silver-copper-titanium active soldering paste

    CN107322187A

  • Preparation method of active metal brazing copper-clad ceramic substrate

    CN113953612A